Ictiólogos de la Argentina : Lauce Rubén Freyre - López, Hugo Luis (2010)
Fil: López, Hugo Luis. División Zoología Vertebrados; Facultad de Ciencias Naturales y Museo; Universidad Nacional de La Plata